2020
DOI: 10.1021/acs.energyfuels.9b04311
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Fluid–Shale Interaction on Salinity: Implications for High-Salinity Flowback Water during Hydraulic Fracturing in Shales

Abstract: Hydraulic fracturing has been widely implemented to enhance hydrocarbon production from shale reservoirs. However, one of the main challenges during hydraulic fracturing is to understand what factor(s) trigger high salinity of flowback water, which sometimes can be up to 300 000 mg/L. While several mechanisms have been proposed to explain the controlling factor behind the high salinity of flowback water, there has been little discussion about the effect of fluid–shale interactions (e.g., mineral dissolution an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 66 publications
0
24
0
Order By: Relevance
“…67 In addition, shale reservoir stimulated by hydraulic fracturing uids tend to contain connate water with relatively high salinity. 68 Prior research indicated some of viscosifying agents such as wormlike micelles lose their viscous characteristics signicantly in the presence of salts. 69,70 Similarly, polymer viscosiers can degrade in the presence of salts.…”
Section: Effect Of Salinity On the Viscosity Of Dbcsmentioning
confidence: 99%
“…67 In addition, shale reservoir stimulated by hydraulic fracturing uids tend to contain connate water with relatively high salinity. 68 Prior research indicated some of viscosifying agents such as wormlike micelles lose their viscous characteristics signicantly in the presence of salts. 69,70 Similarly, polymer viscosiers can degrade in the presence of salts.…”
Section: Effect Of Salinity On the Viscosity Of Dbcsmentioning
confidence: 99%
“…Flowback waters from shale hydraulic fracturing have a high salinity. Fluid-shale interaction can increase the salinity of the fluid to some extent; however, the high salinity of flowback water from hydraulic fracturing of shale is more likely caused by fluid-fluid and fluid-salt interactions (Zeng et al, 2020). Mixing of the injected hydraulic fracturing fluid with saline formation water suggests that pyrite oxidation occurs in fluids that may have varying degrees of salinity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, most of the research did not explain what caused the high salinity of flowback water. The geochemical interaction between shale and fracturing fluid, which affects not only physical properties of the shale but also the composition of the waters produced during shale gas production, is an important controlling factor [13] but rarely has been discussed [30]. Therefore, more studies about the geochemical processes between fracturing fluids and the shale are required to evaluate and minimize the potential environmental impacts.…”
Section: Introductionmentioning
confidence: 99%